Adaptive response to olive cultivation in a generalist parasitic nematode (Meloidogyne javanica). (18th August 2020) - Chapuis, Elodie; Ali, Nadeen; Besnard, Guillaume
Abstract: Cultivated plants usually differ from their wild progenitors in several morphological and/or physiological traits. Their microbe communities might also differ because of adaptation to new conditions related to cultivation. To test this hypothesis, we investigated morphological traits in a parthenogenetic root-knot nematode ( Meloidogyne javanica ) from natural and agricultural environments. Seventeen populations of M. javanica were sampled on cultivated and wild olives in Morocco, then maintained in controlled conditions for a 'common garden' experiment. We estimated the genetic variation based on three traits (stylet size, neck width and body width) by a quantitative genetic design (ten families per population and nine individuals per family were measured), and molecular variation was investigated with a mitochondrial marker to identify the genetic lineages of nematode isolates sampled from wild and cultivated olives. Significant morphological differences were detected between individuals from wild vs. cultivated hosts for the three traits, whereas no phylogenetic clustering was observed among isolates collected on those two hosts. Our results thus suggest an adaptive response of the asexual parasite, possibly related to the deep modification of soil nematode communities between natural olive stands and orchards.